RELIGIOUS FIGURES OF KYRGYZ AND THEIR MODERNIZATION REGARDING ISLAM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the distribution and influence of Islam in the religious faith of the Kyrgyz people. Even if the process of Islamization among the Kyrgyz people lasted a long time, he could not occupy a high position. Even if so, over time, Islam has spread widely among the Kyrgyz people, it has gotten along with ancient traditions and ceremonies, and has penetrated the consciousness of the people. Along with the spread of Islam, Muslim holidays have to a certain extent spread widely in Kyrgyz society. This trend has intensified in particular after the taking of sovereignty. At the same time, Muslim values took over the ancient elements of religious beliefs and preserved them. The article also draws attention to the fact, that compared with other peoples of Central Asia, a number of features are typical of the Kyrgyz people.
Keywords: Islam, Islamization, Muslim holidays, Arab, animism.